The Mediating Role of Critical Thinking Abilities in the Relationship Between English as a Foreign Language Learners’ Writing Performance and Their Language Learning Strategies - Esmaeil Nejad, Maryam; Izadpanah, Siros; Namaziandost, Ehsan; Rahbar, Behzad (Frontiers in Psychology, 2022)
This research investigated the mediation role of critical thinking (CT) about the relationship between the important ways of language learning and EFL learners' writing strategies. The population was 235 Iranian EFL learners. To homogenize the participants, Oxford Placement Test (OPT) was run and 100 intermediate learners were selected. Then, two valid questionnaires of Ricketts’ Critical Thinking Disposition (2003) and Oxford’s (1990) Strategy Inventory for Language Learning were administered. Then, the participants sat for a writing test. The data were analyzed through SPSS (25.00). Results showed that there was a significant relationship between a) learning strategies and learners’ writing performances b) the sub-sets of learning strategies and learners’ writing performances, and c) CT and learners’ learning strategies. However, CT didn’t play a mediating role in the relationship between intermediate EFL learners’ learning strategies and their writing performance. The results may provide insights into helping EFL learners to think and write critically.